2019
DOI: 10.1002/jls.21638
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effect of Ethical Leadership, Moral Identity, and Organizational Identification on Workplace Behavior

Abstract: Ethical leadership encompasses the personal conduct of leaders and leaders’ expectations that followers behave ethically. The two studies presented here draw on moral identity and social identity theories to investigate whether moral identity and organizational identification had an indirect effect on the relation between ethical leadership and organizational outcomes. Study 1 examined how ethical leadership and moral identity interact to influence self‐reported ethical behavior using a sample of 3,363 defense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 45 publications
(71 reference statements)
0
10
0
Order By: Relevance
“…Organizational identification renders organizational attributes such as goals, norms, and values salient and self-defining for individuals and constitutes a fundamental subtext upon which attitudes and behaviors are defined in the organization (Hogg & Terry, 2000;Lee et al, 2015). However, while past work found that ethical leadership may per se facilitate organizational identification (Bedi et al, 2016;O'Keefe et al, 2019;Qian & Jian, 2020;Zhu et al, 2015), we note that the current findings are based on the premise that leaders' ethical conduct is always representative of what the organization stands for (cf. Sluss et al, 2012).…”
Section: Ethical Leadership and Organizational Identificationmentioning
confidence: 61%
“…Organizational identification renders organizational attributes such as goals, norms, and values salient and self-defining for individuals and constitutes a fundamental subtext upon which attitudes and behaviors are defined in the organization (Hogg & Terry, 2000;Lee et al, 2015). However, while past work found that ethical leadership may per se facilitate organizational identification (Bedi et al, 2016;O'Keefe et al, 2019;Qian & Jian, 2020;Zhu et al, 2015), we note that the current findings are based on the premise that leaders' ethical conduct is always representative of what the organization stands for (cf. Sluss et al, 2012).…”
Section: Ethical Leadership and Organizational Identificationmentioning
confidence: 61%
“…In other words, an ethical leader is a leader who is fair, honest, trustworthy, and principled decision-makers that behaves ethically in his/her personal and professional lives (Brown and Treviño, 2006 ; Charoensap et al, 2019 ). Moreover, ethical leaders do not only play the role of moral people by behaving ethically, but they also become moral managers such that they act as role models to influence followers to behave ethically as well (Brown and Treviño, 2006 ; O'Keefe et al, 2019 ). Two theories can rationalize how ethical leaders influence the followers' ethical behavior and standards: social learning theory (Bandura, 1977 ) and social exchange theory (Blau, 1964 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…While doing so, they ensure the enforcement of ethical standards (Peng & Kim, 2020). Thus, they hold employees accountable for their wrong deeds and appraise or punish accordingly (O'Keefe et al., 2019). Such leaders as moral people demonstrate ethical awareness, integrity, honesty, and fairness (Byun et al., 2018).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%